Mechanism of activation of the Nrf2-Keap1 pathway by fermented Chinese herbal medicines via the gut-liver axis to alleviate cadmium-induced hepatotoxicity - Li Jiang; Qiuhong Wu; Yilei Liang; Zhiwen Yang; Guang Fan; Pan Zhou; Xinyue Liu; Yachao Wang (Environmental Chemistry and Ecotoxicology)
Fermented Chinese herbal medicines (FCHM) as green feed additives are environmentally friendly, residue-free, and non-tolerant. The intention of this study was to investigate the mitigating effect of FCHM on cadmium-induced toxicity injury in largemouth bass. The experiment was set up with eight groups of CD (0, 1.024, 1.537, and 2.306 mg/L) and CD + FCHM (0, 1.024, 1.537, and 2.306 mg/L). During the cadmium exposure period, the CD group was fed a basal diet and the CD + FCHM group was fed a basal diet supplemented with 1 % FCHM for 60 days. The results showed that 1 % FCHM decreased the levels of ROS and MDA content, increased the expression of CAT, SOD, and GSH-PX, and alleviated histopathological damage. Additionally, 1 % FCHM activated the Nrf2-Keap1 pathway and decreased oxidative stress, inflammatory response, and apoptosis, while 1 % FCHM upregulated intestinal barrier genes to repair intestinal damage, and 1 % FCHM improved the intestinal flora structure, increased the abundance of Firmicutes, and decreased the abundance of Proteobacteria. Molecular docking showed that GLU, HIS, and ASP residues were important sites for cadmium to exert toxic effects. Meanwhile, multiple active FCHM components alleviated cadmium-induced hepatotoxicity injury by activating the hepatic Nrf2-Krap1 pathway via the gut-liver axis pathway. This study provides new scientific insights and a theoretical basis for the mechanism of FCHM to alleviate the toxicity of heavy metal cadmium